The Influence of 8 and 16 mg Nicotine Patches on Sleep in Healthy Non-Smokers - Jaehne, A.; Unbehaun, T.; Feige, B.; Herr, S.; Appel, A.; Riemann, D. (Pharmacopsychiatry, 2014)
The purpose of this study was to determine whether sleep changes are a consequence of nicotine presence or withdrawal during the night, we examined 66 healthy non-smokers (33 males, 33 females, age: 20–25 years) after an adaptation night in a sleep laboratory setting. Subjects were randomized to receive placebo or either 8 or 16 mg nicotine patches during the day or during the night in a double blind, parallel group design.The 16 mg nicotine patch applied during the night caused a reduced sleep period time and sleep efficiency as well as an increased wake time. A reduced REM-sleep latency and subjective sleep quality rating were found in subjects receiving nicotine during the night. Arousals, apneas and periodic leg movements were not affected by nicotine.This study documents insomnia-like sleep changes in healthy non-smokers caused by nicotine in a dose-dependent manner. There was no evidence for sleep-related withdrawal symptoms after 13 h of nicotine application.
Keywords: sleep; insomnia; smoking; nicotine; leg movements